Analyzing the role of economic globalization in achieving carbon neutrality in Australia. Issue 6 (18th August 2022) - Acheampong, Alex O.; Dzator, Janet; Amponsah, Mary
ABSTRACT: Australia's greenhouse gas emissions have been increasing for over four years, making it difficult to achieve the 2030 agenda to reduce emissions. Also, in recent decades, Australia has been experiencing a rapid increase in economic globalization. The critical question of policy concern is, 'what are the environmental implications of rapid economic globalization in Australia?' This article investigates the asymmetric effect of economic globalization on Australia's carbon emissions using time series data from 1970 to 2018. To achieve the objective of this study, we apply the nonlinear autoregressive distributed lag (NARDL) approach. The results from the NARDL indicated that a positive change in economic globalization contributes to carbon emissions mitigation while a negative change in economic globalization increases carbon emissions. The results disaggregating economic globalization into financial and trade globalization revealed that a positive change in financial globalization reduces carbon emissions while a negative change in financial globalization increases carbon emissions. Contrarily, a positive change in trade globalization increases carbon emissions, while a negative change in trade globalization has a neutral effect on carbon emissions. We suggest that emphasis is required to enhance economic globalization and, specifically, financial globalization to achieve carbon neutrality in Australia.